Plan de mejoramiento para el área de talento humano del grupo empresarial Don Pollo el departamento del QuindÍo (2015)
Don Pollo Business Group now despite being a major source of employment in the department of Quindio, has a high rate of staff turnover which generates a high financial wear and deterioration of the corporate image of the company. This problem was identified mainly due to observation in the direction of human talent in which employees express their withdrawals to long working hours, however it is noted that the selected staff does not meet the characteristics outlined in the job profile. For this it is proposed to make an improvement plan based on internal and external analysis of the company and develop strategies to mitigate the effect of long working hours and redesign the selection process, so that it can perform a control that allows continuous improvement; improvement plan is based on a restructuring of the selection process which currently takes very short form because of the urgency of the staff and the need for production, it is proposed to basically increase the selection filters ensuring strict compliance with profiles occupational and generating technological tools that allow greater proximity to psychometric tests results to staff; and time and motion study that allows for production planning according to product demand monthly. The above strategies seek to exploit the positioning that the company has in the labor and commercial markets, optimize and leverage optimal care currently available financial assets, complying with the decline in the rate of staff turnover and generating a decrease in expenses incurred for recruitment, helping to improve the corporate image